2017
DOI: 10.12816/0047772
|View full text |Cite
|
Sign up to set email alerts
|

Needle Stick Injuries and Compliance among Doctors and Nurses

Abstract: Background: Needle stick injuries (NSI) as an occupational hazard is a concern to employers and health professionals. The literature shows that NSI although a common incident, it is preventable through proper training and routine vaccinations of all hospital employees. Objectives: To determine the incidence of NSI among doctors and nurses in a teaching hospital and the contributing factors towards these injuries. Design: A Cross-Sectional Study. Setting: King Hamad University Hospital, Bahrain. Method: Two dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Most of the injuries occurred after use of the sharps (62.1%) or during use (31.3%) and only a few percent (6.6%) occurred before use (Table 1), which comes in agreement with the study of Hanafi et al, 2011, where most of the injuries (80%) occurred after use (after use and before disposal, recapping and inappropriate or appropriate disposal), and different than results obtained by (Talaat et al, 2003, Lee and Hassim, 2005, Hashmi et al, 2012and Matlab et al, 2017, where more than twothirds of the injury occurred during use of sharps.…”
Section: Discussionsupporting
confidence: 78%
“…Most of the injuries occurred after use of the sharps (62.1%) or during use (31.3%) and only a few percent (6.6%) occurred before use (Table 1), which comes in agreement with the study of Hanafi et al, 2011, where most of the injuries (80%) occurred after use (after use and before disposal, recapping and inappropriate or appropriate disposal), and different than results obtained by (Talaat et al, 2003, Lee and Hassim, 2005, Hashmi et al, 2012and Matlab et al, 2017, where more than twothirds of the injury occurred during use of sharps.…”
Section: Discussionsupporting
confidence: 78%
“…Studies have reported a high rate of Hepatitis B vaccination among HCWs, i.e. 100 % in Iran ( 28 ), 91.5% in India ( 33 ), 88.4% in Lebanon ( 29 ), 77% in Bahrain ( 52 ) and ranged between 62 and 80% in the United Arab Emirates ( 27 , 38 ). This high percentage in our study could be due to the fact that the vaccination is free of charge and the pre-employment checkup exists for all HCWs in KSA.…”
Section: Discussionmentioning
confidence: 99%